Improved River Flood Routing with Spatially Variable Exponent Muskingum Model and Sine Cosine Optimization Algorithm - Atashi, Vida; Barati, Reza; Lim, Yeo Howe (Environmental processes, 2023)
Due to advancements in optimization technology, numerous variable-parameter Muskingum models have been proposed in recent decades, aiming at enhancing the effectiveness of the Muskingum model. However, a knowledge gap exists in understanding the implications of incorporating spatial variations and lateral inflow considerations into the Muskingum model, as well as the performance and applicability of different sub-reach configurations, calling for further research in river flood routing. This study proposed a novel approach to river flood routing using a spatial variable exponent parameter nonlinear Muskingum model with lateral inflow considerations. Unlike previous studies that focused on modifying exponent parameters based on variable inflow levels (i.e., temporal variations), the proposed model considered spatial variations. The proposed Muskingum parameters were estimated using an improved Sine Cosine algorithm (SCA), applied to fit six previously reported case datasets. The proposed method minimized the sum of square errors (SSE) between observed and routed outflows. Results show that the proposed model outperforms others in the Wilson flood case study with an SSE of 6.072 for Number of Sub-reaches (NR)=2, representing an 82.89% reduction compared to NR=1 and constant exponent parameter. Additionally, both the Viessman and Lewis case study and the Dinavar case study demonstrate that NR=3 achieves the best performance and fit to observed data. NR=3 yields the best fit achieving SSE of 9.81 and 2466.62 in the Viessman and Lewis case and the Dinavar case, respectively. The Lawler flood case suggests that a traditional nonlinear model with an SSE of 0.36 for NR=1, 2, or 3 may suffice. Highlights The nonlinear Muskingum model is an extension of the standard Muskingum method. Nonlinear Muskingum Model with Variable Exponent Parameter improves flood routing. The proposed method minimized the sum of square errors (SSE) between observed and routed outflows. The Wilson flood case study demonstrates SSE of 6.072 for NR=2.